DIALEKTIKA BAHASA DAN BUDAYA (Analisis-Sosiologis Terhadap Karya Sastra Arab Periode Klasik) - Abdullah Zainur Rauf (El-QUDWAH, 2006)
Sociologically, literature can not be understood wholly and comprehensively if they are separated from the background of community. Becaouse between literature and the condition of author has dialectics relationship. It means that language can not appreared without contexs whice caused the expression of social-culture’s condition and a history of author’s background. Because, between language and culture have dialectica’s relationship,  both of them can not be separate or language is aculture reflection and aculture phenomenon which language used.